Biochemical characterization of phosphoenolpyruvate carboxykinases from Arabidopsis thaliana - Rojas, Bruno Ezequiel (2019)
ATP-dependent phosphoenolpyruvate carboxykinases (PEPCKs, EC 4.1.1.49) from C4 and CAM plants have been widely studied due to their crucial role in photosynthetic CO2 fixation. However, our knowledge on the structural, kinetic and regulatory properties of the enzymes from C3 species is still limited. In this work, we report the recombinant production and biochemical characterization of two PEPCKs identified in Arabidopsis thaliana: AthPEPCK1 and AthPEPCK2. We found that both enzymes exhibited high affinity for oxaloacetate and ATP, reinforcing their role as decarboxylases. We employed a high-throughput screening for putative allosteric regulators using differential scanning fluorometry and confirmed their effect on enzyme activity by performing enzyme kinetics. AthPEPCK1 and AthPEPCK2 are allosterically modulated by key intermediates of plant metabolism, namely succinate, fumarate, citrate and α-ketoglutarate. Interestingly, malate activated and glucose 6-phosphate inhibited AthPEPCK1 but had no effect on AthPEPCK2. Overall, our results demonstrate that the enzymes involved in the critical metabolic node constituted by phosphoenolpyruvate are targets of fine allosteric regulation.